2017
DOI: 10.1080/17565529.2017.1291400
|View full text |Cite
|
Sign up to set email alerts
|

The climate-development nexus: using climate voices to prepare adaptation initiatives in the Peruvian Andes

Abstract: What are the lessons from development practice that adaptation interventions can use to engage vulnerable people? To answer this question, the paper reviews field data on perceptions of environmental and climatic change in a Peruvian mountain community and discusses the possibilities and limitations of using local climate voices to prepare for climate change adaptation. The data comprise two complementary household surveys. The first survey provides information on the community's socioeconomic situation, whils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
1
19
0
2
Order By: Relevance
“…A systematic, quantitative analysis of literature on the contribution of local knowledge to climate change research by Reyes-Garc ıa et al (2016) shows regional foci in sub-Saharan Africa, the Himalayan range, polar regions, and, to a lesser extent, Southeast Asia. In Latin America, case studies have been conducted, for instance, in Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Nicaragua, and Peru (eg Lagos 2007;Kronik and Verner 2010;Boillat and Berkes 2013;Aldunce et al 2017;L opez et al 2017;Paerregaard 2018). Nonetheless, Reyes-Garc ıa et al (2016) identified weaknesses due to a lack of primary data, incipient methodological development, and unbalanced geographical extent.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic, quantitative analysis of literature on the contribution of local knowledge to climate change research by Reyes-Garc ıa et al (2016) shows regional foci in sub-Saharan Africa, the Himalayan range, polar regions, and, to a lesser extent, Southeast Asia. In Latin America, case studies have been conducted, for instance, in Bolivia, Brazil, Chile, Colombia, Ecuador, Mexico, Nicaragua, and Peru (eg Lagos 2007;Kronik and Verner 2010;Boillat and Berkes 2013;Aldunce et al 2017;L opez et al 2017;Paerregaard 2018). Nonetheless, Reyes-Garc ıa et al (2016) identified weaknesses due to a lack of primary data, incipient methodological development, and unbalanced geographical extent.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cases also show that the state's and the water users' values are not antipodal. Even though to the latter water is a good provided by the mountain deities in return for offerings, they are aware of the impact climate change is having on Peru' water resources (Paerregaard, 2013c(Paerregaard, , 2018b(Paerregaard, , 2019b. As their communities' local water supplies dry up, the water users are increasingly asking the state for assistance to alleviate the growing water shortage, not only by investing in new infrastructure and connecting it to their water supply but also by mediating their internal water disputes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the vulnerabilities that the farmers experience take place within a specific socio-economic context that are besides climate change shaped by history, policies, and markets across multiple scales. Therefore, climate adaptation plans must also carefully consider the implications of such processes on place-specific vulnerabilities they aim to combat (Paerregaard 2018). In the next section, I discuss how Peru's climate adaptation policies (re)shape the vulnerabilities highland farmers' encounter.…”
Section: Smallholders' Vulnerability Experiencesmentioning
confidence: 99%
“…In their view, farmers needed environmental capacitation to get them to abandon inefficient farming practices like "outdated" canal irrigation. While such discourses undermine smallholders' agency to determine their own adaptation needs, they also mask the structural causes of vulnerabilities (Paerregaard 2018). Some farmers, for instance, considered that climate change was a result of local people using too many plastic items, throwing trash in the rivers, and not recycling their waste.…”
Section: Peru's Contradictory Climate Adaptation Effortsmentioning
confidence: 99%